2020
DOI: 10.1007/s40122-020-00212-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Awareness, Attitude and Desire for Labor Analgesia and Associated Factors Among Pregnant Women in Ethiopia: A Cross-Sectional Study

Abstract: Introduction: Labor pain is the worst imaginable pain that women experience during their childbearing years. Untreated labor pain has numerous negative consequences, for both the mother and her fetus. Low levels of awareness and attitudes among pregnant women about labor analgesia is a major challenge that affects outcomes for both the mother and fetus. Therefore, this study aimed to assess the awareness of, attitude towards and desire for labor analgesia and its associated factors among pregnant women who vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 23 publications
4
5
1
13
Order By: Relevance
“…Among the social factors of cesarean section, maternal inability to bear labor pain is the first cause [19]. In addition, some studies have indicated that labor analgesia can reduce the rate of cesarean section, so the promotion of labor analgesia has important social significance to change the current situation of high cesarean section rate in China [20]. is study focuses on the effects of PCEA combined with sufentanil and ropivacaine on maternal analgesia, labor process, and delivery outcome, in order to provide a theoretical basis for the clinical application of labor analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Among the social factors of cesarean section, maternal inability to bear labor pain is the first cause [19]. In addition, some studies have indicated that labor analgesia can reduce the rate of cesarean section, so the promotion of labor analgesia has important social significance to change the current situation of high cesarean section rate in China [20]. is study focuses on the effects of PCEA combined with sufentanil and ropivacaine on maternal analgesia, labor process, and delivery outcome, in order to provide a theoretical basis for the clinical application of labor analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…A frequência encontrada em relação à existência de conhecimento sobre a disponibilidade da analgesia para o parto foi baixa, mas quantitativamente superior à frequência referente a esta mesma variável em estudos semelhantes realizados em países de economia em desenvolvimento, como Etiópia, Uganda e Índia, que apresentaram frequências de 7 a 9,5% (Workie et al, 2021;Nabukenya et al, 2015;Prakash et al, 2017;Naithani et al, 2011). Em outro estudo semelhante, também na Índia, mostrou-se uma frequência mais aproximada à encontrada no presente estudo, mesmo que pequena ainda, de 30% de gestantes em atendimento pré-natal que estavam cientes da existência de analgesia farmacológica para o alívio da dor do parto vaginal (Ponnusamy et al, 2018).…”
Section: Discussionunclassified
“…O fato de as gestantes de países em desenvolvimento desconhecerem a disponibilidade desse modo de alívio farmacológico da dor contribui para a baixa demanda por esse tipo de analgesia. Portanto, em países pobres, o escasso acesso à informação sobre a disponibilidade de determinados cuidados médicos pode influenciar as atitudes em relação ao alívio da dor do parto (Workie et al, 2021). Em um país desenvolvido (Canadá), estudo qualitativo envolvendo parturientes de maternidade de uma comunidade rural mostrou que as gestantes desejavam aprender mais sobre opções de alívio da dor do parto vaginal para fazer uma escolha informada.…”
Section: Discussionunclassified
See 2 more Smart Citations